Organized environmental crime: an analysis of corporate noncompliance with the law - Wolf, Brian Christopher (Edwin Mellen Press, 2009)
Introduction: the problem of corporate crime and the environment -- The theory of corporate illegality and the environment -- Environmental crime and organizational behavior -- Researching organizations and environmental crime -- Results and analysis -- Case studies -- Conclusions and directions for future research